Research on the Types of Textual Emotional Education in Junior High School Chinese Language Teaching - Li, Jinfeng; Liao, Can (Journal of Educational Research and Policies, 2025)
Textual emotion is the most fundamental and important way of emotional education in Chinese language. Teachers should guide students to deeply analyze the text, explore the rich emotions contained in the text itself, and engage in profound emotional dialogue with the text, author, and task. The textual emotional education in junior high school Chinese language teaching mainly includes five types: patriotic sentiment, social phenomena and social ideals, warmth of family, love for life, and personal character. It provides rich teaching resources for emotional education and fully reflects the humanistic nature of Chinese language.